Arthroscopically Assisted Coracoclavicular Fixation Using a Single Flip Button Device Technique: What Are the Main Factors Affecting the Maintenance of Reduction?. (2nd August 2017) - Lee, Yong-Beom; Kim, Jeehyoung; Lee, Ho-Won; Kim, Byung-Su; Yoon, Won-Yong; Yoo, Yon-Sik
Abstract : Background . Among coracoclavicular (CC) fixation techniques, the use of flip button device was demonstrated to have successful outcomes with the advantage of being able to accommodate an arthroscopic procedure. Purpose . This study was conducted to investigate the factors associated with loss of fixation after arthroscopically assisted CC fixation using a single flip button device for acromioclavicular (AC) joint dislocations. Materials and Methods . We enrolled a total of 47 patients (35 men and 12 women). Plain radiography was performed at a mean of 24 months postoperatively to evaluate the final radiological outcome. The primary outcome measure was a long-term reduction of the AC joint for at least 24 months. Results . We found that 29 patients had a high quality reduction (61.7%) and 18 patients had a low quality reduction (38.3%) in initial postoperative CT findings. Our study showed that the duration (5 days) from injury to treatment and the quality of initial postoperative reduction were significantly associated with the maintenance of reduction at final follow-up. Conclusion . Our study showed that maintaining stable reduction after arthroscopically assisted CC fixation using a single flip button device technique is difficult especially in patients who received delayed treatment or whose initial reduction quality was poor.